The enzymatic biosynthesis of acylated steroidal glycosides and their cytotoxic activity - Ming Liu; Jian-Qiang Kong (Elsevier, 2018)
Herein we describe the discovery and functional characterization of a steroidal glycosyltransferase (SGT) from Ornithogalum saundersiae and a steroidal glycoside acyltransferase (SGA) from Escherichia coli and their application in the biosynthesis of acylated steroidal glycosides (ASGs). Initially, an SGT gene, designated as OsSGT1, was isolated from O. saundersiae. OsSGT1-containing cell free extract was then used as the biocatalyst to react with 49 structurally diverse drug-like compounds. The recombinant OsSGT1 was shown to be active against both 3β- and 17β-hydroxyl steroids. Unexpectedly, in an effort to identify OsSGT1, we found the bacteria lacA gene in lac operon actually encoded an SGA, specifically catalyzing the acetylations of sugar moieties of steroid 17β-glucosides. Finally, a novel enzymatic two-step synthesis of two ASGs, acetylated testosterone-17-O-β-glucosides (AT-17β-Gs) and acetylated estradiol-17-O-β-glucosides (AE-17β-Gs), from the abundantly available free steroids using OsSGT1 and EcSGA1 as the biocatalysts was developed. The two-step process is characterized by EcSGA1-catalyzed regioselective acylations of all hydroxyl groups on the sugar unit of unprotected steroidal glycosides (SGs) in the late stage, thereby significantly streamlining the synthetic route towards ASGs and thus forming four monoacylates. The improved cytotoxic activities of 3'-acetylated testosterone17-O-β-glucoside towards seven human tumor cell lines were thus observable. KEY WORDS: Steroidal glycosyltrans ferase, Steroidal glycoside acyl transferase, Ornithogalum saunder siae, Acylated steroidal glyco sides, LacA